Migracje obywateli Ukrainy do Polski w kontekście rozwoju społeczno-gospodarczego: Stan obecny, polityka, transfery pieniężne - Magdalena Lesińska; Małgorzata Grotte; Zuzanna Brunarska (University of Warsaw, Centre of Migration Research (CMR), 2012)
– The paper analyses contemporary inflows of citizens of Ukraine to Poland in the context of socio-economic development of both countries. It consists of three chapters: the first portrays the general patterns and dynamics of Ukrainian migration to Poland including their presence in labour market and in society; the second discusses Polish migration policy and its influence on course and character of Ukrainians' inflows; the third analyses the issue of remittances and their impact on Ukrainian society, economy, and financial sector especially. Each chapter includes the recommendations regarding the possible legal and political changes.
Keywords: 330; migration; Ukrainians; migration policy; money transfers; socio-economic development; Internationale Migration; Migrationspolitik; Migranten; Ukrainer; Rücküberweisungen; Polen